A second domesday? the hundred rolls of 1279-80 - Raban, Sandra (Oxford University Press, 2004)
A comprehensive study of the 1279-80 hundred rolls, one of the most important sources for later 13th century England, this work puts the rolls in their historical context, looks at the way in which the inquiry was conducted and questions whether or not it was conceived as a second Domesday.